Das Verhalten einer holomorphen Funktion bei grossen Werten ihres absoluten Betrages - Nagelė, A. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: A. В. Нагяле, Поведение голоморфной в круге функции при больших значениях ее модуля A. Nagelė. Holomorfinės funkcijos eiga, esant didelėms jos modulio reikšmėms